An appraisal analysis of judgement in vanity fair by william makepeace thackeray - Bùi Ái Ly (Đà Nẵng., 2015)
This thesis examined Judgement, a sub-system of Attitude, which is one of the three semantic systems within the Appraisal theory belonging to the framework of Systemic Functional Linguistics developed by Halliday (1985). The aim of the study is to investigate the judgements used in Vanity Fair by William Makepeace Thackeray (1847) in English. In order to achieve this aim, a combination of the descriptive, quantitative and qualitative approach were used to describe the syntactic and semantic features of Judgement used in the novel Vanity Fair. Specifically, the performance of explicit and implicit judgement were analyzed. 180 samples of Judgement realized by linguistic structures such as adjective phrases, noun phrases, clauses and sentences were collected in the novel Vanity Fair in English. The study found that instances of Judgement were realized with linguistic structures such nominal phrases and adjective phrases in the clause of message in form of both explicit and implicit judgement. Semantically, instances of Judgement were realized in sub-areas of judgement such as social esteem and social sanction which in turn, cover the semantic values of normality, tenacity, capacity, veracity and propriety. Based on the result of data analysis, some implications and suggestions comprehending and using judgement in the novel Vanity Fair in particular and others English literary works in general effectively.
Master thesis in social sciences and humanities
Keywords: appraisal analysis of judgement in vanity fair by william makepeace thackeray; appraisal analysis -- william makepeace thackeray